Ibn Adam(1237AH) his life, and his works - Rashid, Rashid A.; Mustafa, Mohammed S.; Al-Obaidi, Abdulkareem M. H. (Humanities Journal of University of Zakho, 2018)
It is not fair to say that the Kurds are a nation that has always provided humanity with the juice of the minds of its people in various fields and has contributed directly to the building of civilization and civilization since the dawn of true freedom in the world with the mission of the Holy Prophet Muhammad. Ibn Adam al-Balaki al-Rosta'i, who was born in 1160 AH in the village of Rust, in the district of Juman, north of the city of Arbil, the capital. A model of the character of a cosmic corporeal world, a contemporary rule of the Mamluks in the region, and suffered with the people of Kurdistan from the negatives that were surrounding the rule, and the strife and wars that were going on between the two Kurdish emirates Baban and its capital (Qarachulan), and the Suran and its capital (Rawanduz). But this did not stop him from seeking knowledge, he completed his twelve sciences under his father Sheikh Abdullah Al-Balaki, as the Muslim cleric must complete it to become an imam and teacher. Ibn Adam roved between the cities and villages of Kurdistan to the east and south to learn from the scientists, until he became known, and knowledge of his request, the Amir of Rawanduz (Mustafa Bak) to be his adviser, and received the respect of his student Prince (Mohammed AlKabir), which was assigned to the judiciary in the emirate. He was isolated by the Prince two years later because he did not remain silent about injustice. He went to the village of Rust, which witnessed most of his misrepresentations.. Ibn Adam died in 1237 AH in the village of ) Dilza) leaving behind 100 books in the Islamic sciences, the Arabic language, theology, logic, arithmetic, geometry, history and astrology. It has been found in public libraries in Sulaymaniyah and Baghdad, and private libraries such as the library of his grandson dr. Abdullah Al Mulla Saeed, and others on (69) his manuscript only.